SISTEM PENGONTROLAN MOTOR DC DAN KATUP OTOMATIS - Erlina Erlina; Carolus Borromeus S (Sekolah Tinggi Teknik PLN, 2015)
AT89S52 microcontroller to control a dc motor that serves as a water pump motor and automatic valves as water entry and exit control, application control, the writer intended as a simulation of filling water in a bucket or tub in open loop through an intermediary medium sms which also serves as a giver of orders, which later when refined into a closed loop can be applied for filling the boiler tank in plants - power plants.